Application of IoT in Healthcare (International Journal of Innovative Research in Computer Science & Technology, 2021)
There has been a lot of research into  medical facilities and technological developments during  the last ten years. To be more specific, the Internet (IoT)  has shown promise in connecting a range of healthcare  gear, monitors, and hospital professionals in order to  provide high medical treatment at a remote location.  Patient safety has increased, medical costs have fallen,  medical solutions have becoming increasingly available,  and efficiency in the healthcare business has increased.  The current study presents an up-to-date review of the  potential healthcare uses of IoT-based technology. This  article describes the advancement of the utilization of the  Hospital IoT in solving various healthcare challenges  from the perspectives of enabling technology, medical  providers, and applications. Furthermore, potential  Healthcare IoT system problems and issues are addressed.  To summarize, the current research provides a  comprehensive resource of knowledge on the different  applications of Healthcare IoT, with the purpose of aiding  future academics engaged in studying in the area to have  a better understanding of the issue.
Keywords: Application; Healthcare; IoT; Technology